TRANSNATIONAL MIGRATION AND ETHNIC ENTREPRENEURSHIP AMONG THE CHAM DIASPORA IN MALAYSIA - Betti Rosita Sari (Jurnal Kajian Wilayah, 2017)
This article is concerned with the Cham diaspora in Malaysia, who maintain transnational ties to their home land of “Kampong Cham” in Cambodia. With the process of movement and resettlement, this community confronted real challenges and had to develop new ways of life in a new milieu. From traditional forms of farming and fishing, which had been their main sources of economic support in Cambodia, these people transformed their main traditional activities to develop commercially-oriented economic activities in their new settlement.This paper aimed to answer two questions, first, how migrants use patron client relationships to survive and pursue their life in Malaysia. Second, how Cham diaspora in Malaysia who take the role of ethnic entrepreneur or patron help other migrants to negotiate transnational space and therefore facilitate transnationalism. This ethnic network plays an important role in their ethnic businesses and economic survival strategy, both for the previous migrant and new comer migrants. This paper contributes to a contemporary issue of Cham diaspora in Malaysia, one of ethnic minority in Cambodia and their strategy to face globalization by establishing transnational networking.  Keywords: Diaspora, Cham, transnational migration, entrepreneurship, ethnic network, Malaysia AbstrakArtikel ini berkaitan dengan diaspora Cham di Malaysia, yang mempertahankan hubungan transnasional dengan tanah asal mereka "Kampong Cham" di Kamboja. Dengan proses perpindahan dan pemukiman kembali, komunitas ini menghadapi tantangan nyata dan harus mengembangkan cara hidup baru di lingkungan baru. Dari bentuk tradisional pertanian dan perikanan, yang merupakan sumber utama dukungan ekonomi mereka di Kamboja, orang-orang ini mengubah kegiatan tradisional utama mereka untuk mengembangkan kegiatan ekonomi berorientasi komersial di pemukiman baru mereka. Makalah ini bertujuan untuk menjawab dua pertanyaan, pertama, bagaimana migran menggunakan hubungan klien patron untuk bertahan dan mengejar kehidupan mereka di Malaysia. Kedua, bagaimana Cham diaspora di Malaysia yang mengambil peran pengusaha etnis atau pelindung membantu migran lainnya untuk menegosiasikan ruang transnasional dan karena itu memfasilitasi transnasionalisme. Jaringan etnik ini memegang peranan penting dalam bisnis etnik dan strategi bertahan hidup ekonomi mereka, baik bagi pendatang migran migran sebelumnya maupun pendatang baru. Makalah ini berkontribusi pada isu kontemporer Cham diaspora di Malaysia, salah satu etnis minoritas di Kamboja dan strategi mereka untuk menghadapi globalisasi dengan membangun jaringan transnasional. Kata kunci: Diaspora, Cham, migrasi transnasional, kewirausahaan, jaringan etnik, Malaysia